Valve bone woe [compact disc] - Hynde, Chrissie; Hynde, Chrissie (BMG Rights Management (UK) Ltd., 2019)
Chrissie Hynde of the Pretenders releases a jazz album that features covers of songs from Brian Wilson, John Coltrane, Charlie Mingus, Frank Sinatra, and more.